Karakteristik Pasien Tumor Orbita Di PMN RS Mata Cicendo Bandung Periode 2017-2018 - Ira Citra Ningrom; Andi Muh. Maulana; Susiyadi Susiyadi; Raudatul Janah (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2021)
Orbital tumors are tumors that occur in the orbital area where they can affect the outside of the orbit and the inside of the orbit. At present, it is still rare to report the prevalence of orbital tumors in the world. In developing countries such as Indonesia, reports on the incidence of orbital tumors are also rarely reported. Diagnosis and appropriate therapy if we recognize the characteristics of these orbital tumors. The purpose of this study was to determine the characteristics of orbital tumor patients at PMN Cicendo Eye Hospital Bandung. This research is a descriptive observational study with cross sectional method with total sampling technique. Data were collected retrospectively based on medical records in the form of age, sex, eyes involved, tumor location, surgery, clinical diagnosis, and histopathological results. The results showed that orbital tumors with the majority of age> 45 years (43.3%), male gender (55.4%), involvement of the left ocular eye (51.18%), with the most frequent location not in the conjunctiva, palpebral and retrobulbar (36.8%), clinical diagnosis of benign tumors (68.3%) were cysts (22.4%), the most histopathological results of benign tumor lesions (71.4%) were inflammation (17%). So it can be concluded that knowing the characteristics of this orbital tumor will have an impact on the therapy given will be appropriate.